Motivations, opportunities, and challenges of Afghan immigrant students in Iranian universities: A qualitative inquiry - Rabiei-Kashanaki, Maryam; Pourebrahimi, Mohammad; Khodabakhshi-Koolaee, Anahita (Journal of International Students, 2025)
This study investigated the psychosocial experiences of Afghan immigrant students enrolled in Iranian universities, with a focus on their motivations for academic migration, the opportunities available to them in academic and social spheres, and the challenges they face both in their educational trajectories and daily lives. This qualitative study employed a conventional content analysis approach and was conducted in Tehran in 2024. Data were collected through semi-structured interviews with 11 purposively selected Afghan students studying in Iran. Data analysis revealed four main themes: (1) Motivations for Leaving the Homeland and Pursuing Personal Growth, (2) Socioeconomic Constraints, (3) Psychological Challenges of Migration, and (4) Opportunities and Positive Outcomes of Migration. The findings highlighted the urgent need for enhanced psychological, social, and academic support systems for immigrant students to improve their overall experience. The study calls for the development of comprehensive support programs and the implementation of sustainable policy measures.